An Audit of Post Operative Complications of Elective Abdominal Hysterectomies (Medical Forum Monthly, 2024)
Objective: To record common post operative complications their risk factors. Place and Duration of Study: Obstetrics and Gynaecology unit of DHQ hospital Timergara lower Dir, from 1/01/2006 till 30/12/2006. Method: The complications were recorded on a pre constructed Performa showing demographic data of patient, history, general health, indication for operation and surgeon rank. The Patients were divided in to three groups: A, B & C. Group – A: Complications occurring after operation with in the first 72 hours. Group – B: Complications occurring after and 72 hours but with in hospital stay Group – C: And complications recorded at follow up visit after 6 weeks. Results: Our study showed the over all complications rate of 48.7% which is a significant rate, mortality were 4 out of 478 cases (8.36/1000). Conclusion: The rate of complications was high in those women who had other associated medical problems, which can be reduced or avoided by Proper Pre-operative assessment, management and Technical factors under surgeon’s control.